Rural-Urban Migration in the Maghreb - Ospina, Gloria Inés (UNISCI Discussion Papers, 2014)
Internal migration flows from rural to urban areas have been considered one of the leading factors in the creation of regional imbalances where they occurred. The world is becoming more urban, and this implies that the activities of the city attract many people, which inevitably come from rural areas. In the present case, the phenomenon of rural exodus has been considered as a challenge to all the agricultural reforms implemented by the Maghreb countries in their short period of life since independence. The article explains the results obtained with the reforms and stress that rural-urban migration flows continue and will continue in the next coming years.